Workshop Penguatan Peran Keluarga dan Masyarakat dalam Mendukung Kota Ramah Anak - Sugiarti, Tri; Amriani H, Sri Rika; Parwoto, Parwoto; Asti, A. Sri Wahyuni; Pratama, Muhammad Isbar (Universitas Negeri Makassar, 2025)
The Workshop on Strengthening the Role of Families and Communities in Supporting Child-Friendly Cities was conducted to enhance community capacity in creating environments that support children's growth and development. This activity used a participatory research-based approach and was implemented through five stages: needs identification, material planning, workshop implementation, evaluation, and follow-up. The results showed an increase in participants' understanding of child-friendly city concepts, positive parenting, and community roles. Evaluation using pre-test and post-test showed an average score improvement of 24.9 points. Twenty out of twenty-six participants created community action plans such as reading corners, neighborhood-based parenting groups, and supervised play areas. These findings indicate that a participatory educational approach can foster awareness and collective commitment to sustainably support child-friendly cities.